2016
DOI: 10.1080/14767058.2016.1187125
|View full text |Cite
|
Sign up to set email alerts
|

3D and 2D ultrasound-based fetal weight estimation: a single center experience

Abstract: Fractional limb volume method is a very promising method for fetal weight estimation. Its performance is not significantly different from the modified Hadlock method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A study of over 9000 singleton pregnancies investigated the effect of maternal age, weight, height, parity, diabetes, fetal sex, presentation, amniotic fluid index and sonographer experience; it was concluded that, although some of these factors had a significant effect on EFW, their contribution was small and of questionable clinical significance. There is some contradictory evidence for whether the precision of EFW can be improved by three‐dimensional (3D) ultrasound volumetry. Recent evidence suggests that EFW using magnetic resonance imaging (MRI) may be more accurate than ultrasound in the prediction of both SGA and LGA neonates.…”
Section: Discussionmentioning
confidence: 99%
“…A study of over 9000 singleton pregnancies investigated the effect of maternal age, weight, height, parity, diabetes, fetal sex, presentation, amniotic fluid index and sonographer experience; it was concluded that, although some of these factors had a significant effect on EFW, their contribution was small and of questionable clinical significance. There is some contradictory evidence for whether the precision of EFW can be improved by three‐dimensional (3D) ultrasound volumetry. Recent evidence suggests that EFW using magnetic resonance imaging (MRI) may be more accurate than ultrasound in the prediction of both SGA and LGA neonates.…”
Section: Discussionmentioning
confidence: 99%
“…US operator training and audit is unlikely to improve measurement errors within US-EFW calculations significantly; thus, development of alternative methods is required [6]. 3D-US has shown some promise however has not been routinely adopted in the clinical setting because it is yet to be evidenced as being more reliable than 2D-US biometric methods [20][21][22]. The primary aim of this study was to compare the agreement and reliability of US and MRI to measure the EFW in the second trimester and a secondary aim to assess the feasibility of the MRI-EFW in cases of extreme prematurity.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts at improving the prediction of birth weight by the addition of maternal characteristics to fetal biometry have not been found to be successful 24,25 . Similarly, there is some contradictory evidence as to whether the precision of EFW can be improved by three-dimensional ultrasound volumetry [26][27][28] . Second, development of a standardized fetal biometric ultrasound measurement protocol, involving training, assessment and certification of sonographers and both qualitative and quantitative quality-control monitoring, can minimize systematic error and ensure high reproducibility 21 .…”
Section: Discussionmentioning
confidence: 99%